Prescription omega-3 fatty acid products containing highly purified eicosapentaenoic acid (EPA). Issue 1 (December 2017) - Brinton, Eliot; Mason, R.
Abstract The omega-3 fatty acid eicosapentaenoic acid (EPA) has multiple actions potentially conferring cardiovascular benefit, including lowering serum triglyceride (TG) and non-high-density lipoprotein cholesterol (non-HDL-C) levels and potentially reducing key steps in atherogenesis. Dietary supplements are a common source of omega-3 fatty acids in the US, but virtually all contain docosahexaenoic acid (DHA) in addition to EPA, and lipid effects differ between DHA and EPA. Contrary to popular belief, no over-the-counter omega-3 products are available in the US, only prescription products and dietary supplements. Among the US prescription omega-3 products, only one contains EPA exclusively (Vascepa); another closely related prescription omega-3 product also contains highly purified EPA, but is approved only in Japan and is provided in different capsule sizes. These high-purity EPA products do not raise low-density lipoprotein cholesterol (LDL-C) levels, even in patients with TG levels >500 mg/dL, in contrast to the increase in LDL-C levels with prescription omega-3 products that also contain DHA. The Japanese prescription EPA product was shown to significantly reduce major coronary events in hypercholesterolemic patients when added to statin therapy in the Japan EPA Lipid Intervention Study (JELIS). The effects of Vascepa on cardiovascular outcomes are being investigated in statin-treated patients with high TG levels in the Reduction of Cardiovascular Events With EPA-Intervention Trial (REDUCE-IT).